Hand shape and proportions of students of the Medical Academy in Bialystok - Jelisiejew , Tamara; Korszun, Elzbieta (Anthropological Review, 1975)
Outlines of both hands of 236 students in their I-st year (93 men and 143 women aged 18 - 21), were measured for width, length, and type according to the proportions of the fingers. Applying statistical methods, it was found that male students have on the average hands of larger dimensions than females. The hands of male students are proportionally larger and shorter than those of female students. whose hands are slimmer. With regard to proportions of the fingers, it was found that most frequently, in both sexes, a cubital type of hand occurs: finger 4>2; then the intermediary type: 4=2; and most seldom, the radial type 4<2.